Sistem Pakar Mendiagnosa Penyakit Microcephaly Menggunakan Metode Rete - Uliana Tarigan (STMIK Budi Darma, 2022)
An expert system for diagnosing Microcephaly is one of the important things considering the disease that needs to be observed so that this disease is easy to attack children. The problem that became the starting point in making this thesis is how to solve the problem using the Rete method. From the analysis, it can be seen that the expert system for diagnosing Microcephaly can be done using the Rete method using a computer program that suits the needs, so that users can get better diagnostic results more easily. With the existence of an expert system for diagnosing Microcephaly, it is hoped that it will make it easier to see, the symptoms, causes and results of the diagnosis of Microcephaly. In designing this diagnosis using Microsoft Visual Basic 2008